Hasil Microgreen Sawi Sendok pada Media Tanam Rockwool Menggunakan Pupuk ABmix, Pupuk Organik Cair Nasa dan Pupuk Pemacu Tumbuh Hormonik - Abdullah Sarijan; Irba Djaja; Kurniawan Dwi AS; M Asvad B Majid; Diva Aulia Farahningtyas; Halana Syari; Fitri Ramadhani; Sri Anjani; Nurhening Y Ekowati (Universitas Wahid Hasyim, 2025)
Microgreens are nutrient-rich vegetables with a very short harvest life. Compared to mature vegetables, microgreens have a higher nutritional content. Besides that, microgreens are generally free from chemical pesticide contamination and are considered a very healthy food ingredient. This research aims to determine how fertilization influences the growth and yield of spoon mustard microgreens grown using rockwool media. The study was carried out at the Agrotechnology Laboratory at Universitas Musamus-Merauke from August to September 2024. The results of the study showed that fertilization influenced microgreen height, hypocotyl length, and hypocotyl diameter and had no effect on observations of the number of leaves and weight of 10 microgreens. In general, there is a tendency to use ABMix fertilizer as a source of nutrition to provide better growth and results. Keywords: Bokcoy, healthy vegetables, microgreens